SACRIFICIAL ANODE CATHODIC PROTECTION OF LOW CARBON STEEL IN SEA WATER - Aprael S. Yaro; Khalid W. Hameed (Journal of Engineering, 2006)
Cathodic protection is a corrosion-prevention technique which uses the electrochemical properties of metals to insure that the structure to be protected becomes the cathode of an electrolytic cell Laboratory evaluation was conducted on zinc electrode as anode material that used for sacrificial anode cathodic protection (SACP)of carbon steel. Rate of zinc consumption during cathodic protection of carbon steel pipeline carrying seawater (4 % w/v NaCl solution) were measured by the loss in weight technique. Variables studied were seawater temperature (0-45o C), flow rate (5-900 lit/h), pH (2-12) and duration time (1-4 h). It was found that the rate of zinc consumption increases with increasing seawater temperature, flow rate and duration time and decreases with pH increase. Under the mentioned operating conditions, the rate of zinc consumption during cathodic protection of steel ranged from 5.65×10-3 to 98.9×10-3 g/cm2 .day. For the system under investigation, the cell responsible for cathodic protection is Zn/NaCl/Fe.